Напрями покращення мотиваційного менеджменту в аграрних підприємствах - Демидова, Марія Миколаївна; Demydova, Mariia (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
В статті наведено основні напрями покращення мотиваційного менеджменту в аграрних підприємствах. Проаналізовано вплив мотиваційного менеджменту на стан використання та розвиток трудових ресурсів агарних підприємств. Визначено основні ризики використання трудових ресурсів та групи чинників, що сприяють ефективному їх використанню. В статті висвітлено основні резерви для подальшого розвитку і підвищення ефективності мотиваційного менеджменту в аграрних підприємствах. Встановлено фактори результативності покращення мотиваційного менеджменту в аграрних підприємствах на макро- та мікрорівнях. Доведено необхідність та описано процес моделювання мотиваційного менеджменту відповідно до етапів життєвого циклу агарного підприємства. Розроблено модель мотиваційного менеджменту аграрного підприємства. Виділено рівні задоволення потреб працівників аграрного підприємства на основі взаємодії та взаємодоповнення матеріального та нематеріального мотивування. The article gives the main directions of improvement of motivational management in agrarian enterprises. The influence of motivational management on the state of use and development of labor resources of agrarian enterprises is analyzed. The main risks of using labor resources in agrarian enterprises are determined. The necessity of training, retraining of labor resources, financing of studies, use of such a concept of human management as "tactics of orders", increase of employees' income for improving the state of labor utilization and situation in the field of motivational management is proved. The basic groups of factors are determined, the coordinated use of which helps to efficiently use labor resources in agrarian enterprises. The main requirements for recognition of the system of motivational management are highlighted. The factors of effectiveness of improving the motivational management in agrarian enterprises at macro and micro levels have been established. The reserves for further development and increase of the efficiency of motivational management in agrarian enterprises are highlighted and grouped. Attention, however, focuses on improving the organization of work, which includes the expansion of production functions and improvement of working conditions, the use of flexible schedules. The article proves the necessity of modeling motivational management taking into account the interests of the state, enterprises, employees, consumers and suppliers. The process of modeling of motivational management in accordance with stages of the life cycle of the agrarian enterprise is described. The model of motivational management of the agrarian enterprise is developed and the main factors of motivation are defined at each stage of the life cycle of the enterprise. The level of satisfaction of the needs of the employees of the agrarian enterprise is determined on the basis of interaction and complementarity of material and non-material motivation. Recommendations on the use of various tools of motivational management for satisfying the needs of different levels and ultimately for the effective functioning of the system of motivational management are given.
Directions of improvement of motivational management in agrarian enterprises
Keywords: мотиваційний менеджмент; motivational management; трудові ресурси; labor resources; аграрне підприємство; agrarian enterprise; мотивація; motivation; потреби; needs